Synergistic effects of probiotics with soy protein alleviate ulcerative colitis by repairing the intestinal barrier and regulating intestinal flora - Rentang Zhao; Bingqing Shang; Luyan Sun; Suyuan Lv; Guolong Liu; Qiu Wu; Yue Geng (Journal of Functional Foods, 2024)
In this experiment, we used probiotic and soy protein as raw materials to intervene in DSS-induced acute ulcerative colitis in C57BL/6 mice, to investigate the mitigating effect and synergistic effect of the probiotic complex combined with soy protein. The results showed that the combination of probiotics and soy protein could effectively alleviate the symptoms in UC mice, and inhibit the inflammatory process by down-regulating the expression of IL-6 and TNF-α and reducing the infiltration of inflammatory cells. Histopathological results showed that probiotic and/or soy protein interventions were effective in reducing the DAI of colonic ulceration, repairing intestinal epithelial barrier damage, and up-regulating the expression of tight junction-associated proteins. The composition of intestinal microbiota in the SP group, YWSP group and SNSP group with soybean protein intervention showed similar characteristics. In conclusion, the combination of YW probiotic powder and soy protein exerted a good synergistic effect.